Hydride phase formation in carbon supported palladium hydride nanoparticles by in situ EXAFS and XRD. (May 2016) - Bugaev, A L; Guda, A A; Lomachenko, K A; Lazzarini, A; Srabionyan, V V; Vitillo, J G; Piovano, A; Groppo, E; Bugaev, L A; Soldatov, A V; Dmitriev, V P; Pellegrini, R; et al.
Abstract: In the current work we present a detailed analysis of the hydride phase formation in industrial Pd/C nanocatalysts by means of combined in situ X-ray absorption spectroscopy (EXAFS), X-ray diffraction (XRD) and volumetric measurements for the temperatures from - 10 to 50 °C in the hydrogen pressure range from 0 to 1000 mbar. α- and β- hydride phases are clearly distinguished in XRD. For the first time, H/Pd atomic ratio were obtained by theoretical fitting of the near-edge region of the absorption spectra (XANES) and compared with volumetric measurements.